2021
DOI: 10.1200/jco.2020.39.28_suppl.162
|View full text |Cite
|
Sign up to set email alerts
|

Examining social media peer support and improving psychosocial outcomes for young women with breast cancer.

Abstract: 162 Background: Young women with breast cancer (YWBC) have unique survivorship needs due to life stage at point of diagnosis. Peer support sought by YWBC through social media channels appears to be rising. We aimed to understand the unmet needs of YWBC in order to develop a tailored peer support program to improve young women’s breast cancer experience and ultimately reduce psychosocial morbidity long-term. Methods: Using qualitative inquiry, we conducted semi-structured interviews with YWBC survivors and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The participants did not receive sufficient empathy from family and friends who had not experienced the disease and felt marginalized even among other patients with breast cancer because of their young age. This finding is consistent with young women with breast cancer experiencing discomfort amid mixed-age groups, 43 contrary to general beliefs that self-help groups composed of patients with the same disease provide psychosocial support. 44 To address these challenges and fulfill their psychosocial needs, the participants engaged in online chats to communicate, empathize, and encourage peers in their age group.…”
Section: Discussionsupporting
confidence: 82%
“…The participants did not receive sufficient empathy from family and friends who had not experienced the disease and felt marginalized even among other patients with breast cancer because of their young age. This finding is consistent with young women with breast cancer experiencing discomfort amid mixed-age groups, 43 contrary to general beliefs that self-help groups composed of patients with the same disease provide psychosocial support. 44 To address these challenges and fulfill their psychosocial needs, the participants engaged in online chats to communicate, empathize, and encourage peers in their age group.…”
Section: Discussionsupporting
confidence: 82%
“… 6 , 9 However, general peer support groups, predominantly comprising women at later life stages, fail to address the distinct needs of young women with breast cancer. 10 These young women exhibit heightened risk perceptions of cancer recurrence, 11 higher levels of depression and anxiety, 12 and experience unique psychosocial demands related to work, finance, fertility, and family and social relationships. 12 , 13 Therefore, peer support specific to the unique needs of young women with breast cancer should be offered.…”
Section: Introductionmentioning
confidence: 99%
“…However, Smailhodzic et al [ 26 ] found high engagement with posts in this category, often generating empathetic responses from other users. Though these types of interactions often had low generativity (i.e., did not often generate new ideas), social media support can provide users with shared experience, understanding, hope, and increased confidence and healthcare navigation in this way [ 28 ].…”
Section: Discussionmentioning
confidence: 99%